Exploring Input Parameters in an Expressive Vocabulary Treatment With Late Talkers - Alt, Mary (J Speech Lang Hear Res, 2020)
PURPOSE: The aims of this study were (a) to assess the efficacy of the Vocabulary Acquisition and Usage for Late Talkers (VAULT) treatment and (b) to compare treatment outcomes for expressive vocabulary acquisition in late talkers in 2 conditions: 3 target words/90 doses per word per session versus 6 target words/45 doses per word per session. METHOD: We ran the treatment protocol for 16 sessions with 24 primarily monolingual English-speaking late talkers. We calculated a d score for each child, compared treatment to control effect sizes, and assessed the number of words per week children acquired outside treatment. We compared treatment effect sizes of children in the condition of 3 target words/90 doses per word to those in the condition of 6 target words/45 doses per word. We used Bayesian repeated-measures analysis of variance and Bayesian t tests to answer our condition-level questions. RESULTS: With an average treatment effect size of almost 1.0, VAULT was effective relative to the no-treatment condition. There were no differences between the different dose conditions. DISCUSSION: The VAULT protocol was an efficacious treatment that has the potential to increase the spoken vocabulary of late-talking toddlers and provides clinicians some flexibility in terms of number of words targeted and dose number, keeping in mind the interconnectedness of treatment parameters. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.11593323